Intracellular targets: A multiple cargo transporting molecule. (15th June 2021) - Papadopoulos, Christos; Fotou, Evgenia; Moussis, Vassilios; Ntoyhaniari, Alaxandra; Zografou, Sofia; Maltabe, Violetta; Kouklis, Panos; Christoforidis, Savvas; Tsikaris, Vassilios
Abstract : The generation of cell‐penetrating peptides as cargo‐delivery systems has produced an immense number of studies owing to the importance of these systems as tools to deliver molecules into the cells, as well as due to the interest to shed light into a yet unclear mechanism of the entrance of these peptides into the cells. However, many cell‐penetrating peptides might present drawbacks due to causing cellular toxicity, or due to being entrapped in endosomes, or as a result of their degradation before they meet their target. In this work, a cargo transporting molecule, the Cell Penetrating Sequential Oligopeptide Carrier (CPSOC), formed by the repetitive ‐Lys‐Aib‐Cys‐ moiety, was tested for its ability to penetrate the cell membrane and transport the conjugated peptides into the cells. The cysteine residue anchors bioactive molecules through a stable thioether bond. The lysine supplies the positive charge to the construct, whereas the α‐amino isobutyric acid is well known to induce helicoid conformation to the peptide backbone and protects from enzymatic degradation. The present study demonstrates that CPSOC penetrates the membrane transporting the conjugated cargo into the cell. When we tested CPSOC‐conjugated peptides carrying critical domains of Cdc42, a small GTPase implicated in exocytosis, the internalized peptides were found to be functional because they inhibited exocytosis of von Willebrand factor from endothelial Weibel–Palade bodies a trafficking event depending on the Cdc42 protein. The data suggest that the carrier can deliver efficiently functional peptides into the cells, and thus, it can be used as a multiple‐cargo transporting molecule. Abstract : CPSOC can bind up to four copies of biocargoes via thioether bonds and transport them into the cells.